ANALYSIS ANALYSIS OF ASH CONTENT AND ACID NUMBER TEST IN WASTE COOKING OIL AFTER REFINING USING SUGAR CANE BAGASSE: ANALISIS UJI KADAR ABU DAN BILANGAN ASAM PADA MINYAK JELANTAH SETELAH PEMURNIAN MENGGUNAKAN AMPAS TEBU - savitri, nava (Jurnal Kesehatan Ilmiah Aufa Royhan, 2024)
Used cooking oil is a waste product containing high free fatty acids due to repeated heating, requiring purification to improve its quality. This study aimed to analyze the effectiveness of sugarcane bagasse-derived activated carbon as an adsorbent in reducing the acid value of used cooking oil. The research employed an experimental design using a completely randomized approach, with variations in adsorbent type (raw bagasse and activated bagasse charcoal) and soaking duration (1x24 hours to 4x24 hours). The results indicated that activated bagasse charcoal was more effective than raw bagasse, achieving the lowest acid value of 0.448 mg KOH/g after a 4x24-hour soaking period. The activated carbon met SNI 06-3730-1995 standards, with an average ash content of 0.7925%, and significantly reduced the acid value of used cooking oil. This study recommends the use of sugarcane bagasse-derived activated carbon as an eco-friendly solution for refining used cooking oil.